Eye and Orbit Injuries Caused by Electric Scooters and Hoverboards in the United States - Ruan MZ; Meer E; Kaur G; Namiri NK; Ashraf DC; Winn BJ; Kersten R; Vagefi MR; Grob S (Clinical Ophthalmology, 2024)
Merry ZC Ruan,1,2 Elana Meer,1,2 Gurbani Kaur,2 Nikan K Namiri,2 Davin C Ashraf,3 Bryan J Winn,1,4 Robert Kersten,1,4 M Reza Vagefi,1,4 Seanna Grob1,4 1Department of Ophthalmology, University of California, San Francisco, San Francisco, CA, USA; 2Department of Medicine, University of California, San Francisco, San Francisco, CA, USA; 3Division of Oculofacial Plastic and Orbital Surgery, Department of Ophthalmology, Oregon Health & Sciences University, Portland, OR, USA; 4Division of Oculofacial Plastic and Orbital Surgery, Department of Ophthalmology, University of California, San Francisco, San Francisco, CA, USACorrespondence: Seanna Grob, Department of Ophthalmology, Academic Director, Oculofacial Plastic and Orbital Surgery, University of California, San Francisco, San Francisco, CA, USA, Tel +1 858-349-1813, Fax +1 415-476-0336, Email seanna.grob@ucsf.eduIntroduction: To evaluate eye and orbital injuries in non-powered scooter, electric-scooter (e-scooter), and hoverboard riders in the United States (US) between 2014 and 2019.Methods: The National Electronic Injury Surveillance System (NEISS) was queried for head and neck injuries by body part codes related to non-powered scooters and powered scooters/hoverboards from 2014 to 2019. The NEISS complex sampling design was used to obtain US population projections of injuries and hospital admissions. Keywords were queried in case narratives to analyze trends in location, type, and mechanism of eye and orbit injuries.Results: Since their introduction, a 586% (p=0.01) increase in e-scooter injuries and 866% (p< 0.001) increase in hoverboard injuries were observed with an increase in hospital admissions seen in young adults (18– 34) in urban areas (e-scooter: 5980% and hoverboard: 479%). Descriptive narratives of the trauma noted eye injuries in 242 unweighted NEISS cases with only 30 cases appropriately documented under body part code 77: eyeball. Eye injuries increased 96.9% during the study period (p=0.23). Specifically, the most common ophthalmic injuries reported included eyebrow (40.9%) and eyelid (11.3%) lacerations, periorbital contusions (18.7%), orbit fractures (6.6%), and corneal abrasions (5.1%).Conclusion: There was a significant increase in both head and neck injury cases and hospital admissions related to e-scooters. Eye and orbit injuries similarly increased but were underreported by body part code compared to injury narratives. Orbital fractures were reported more frequently in injuries from e-scooters than non-powered scooters.Plain language summary: From 2014 to 2019, there were significant increases in both head and neck injuries and hospital admissions related to e-scooters, with eye and orbital injuries similarly increased but underreported by body part code compared to the injury narratives.Keywords: scooter, e-scooter, electric scooter, hoverboard, eye trauma, orbital fracture, orbit